Transportation and quality assurance system in agricultural sector - Atadjanova Zulfiya; Kadirova Sharofat; Murodov Abduraxim (E3S Web of Conferences)
The purpose of this article is to describe a system of indicators characterizing the quality of transport services and to create its model. Since the indicators that ensure the quality of transport services are interdependent, each of them requires a separate approach. To adapt to changing customer demands, it is necessary to present metrics within a holistic model, establish a service standard, and analyze how far actual services have deviated from the standard. If the shift is negative for the transport company, clients, partners, it is necessary to make a decision and develop measures to correct it through measures. As one of the convenient forms of assessing the system of indicators, it is worth highlighting the full implementation of new technologies in the field of transport.